Exploiting transposons in the study of Staphylococcus aureus pathogenesis and virulence. (4th May 2023) - Ong, Zi Xin; Kannan, Bavani; Becker, David L.
Abstract: The opportunistic pathogen Staphylococcus aureus has an extremely complex relationship with humans. While the bacteria can exist as a commensal in many, it can cause a wide range of diseases and infections when turned pathogenic. Its presence is a determinant of chronicity and poor prognosis in numerous diseases, and its genomic plasticity causes S. aureus antimicrobial resistance to be one of the most dire contemporary medical problems to solve. Genetic manipulation of S. aureus has led to numerous findings that are vital in the fight against its pathogenesis. The utilisation of transposon mutant libraries for the systematic inspection of the S. aureus genome led to many landmark discoveries pertaining to the bacteria's pathogenicity, antimicrobial resistance acquisition, and virulence regulation. In this review, we describe mutant libraries, and their significant contributions, from various S. aureus strains created with commonly used transposons. The general workflow for the construction of libraries will be presented, along with a discussion of the challenges of undertaking the task of large-scale library construction. As the accessibility of transposon mutant library construction, screening, and analysis increases, this genetic tool could be further exploited in the study of the S. aureus genome.